Pinus KERAGAMAN MORFOTIPE FUNGI EKTOMIKORIZA PADA HUTAN PINUS (Pinus merkusii Jungh. & de Vriese) DI KEBUN RAYA KENDARI - basrudin basrudin (Jurusan Kehutanan -FHIL-UHO, 2023)
Kendari Botanical Garden is an ex situ plant conservation area that has the functions of conservation, research, education, tourism and environmental services. In the area there are many pine trees (Pinus merkusii Jungh. & de Vriese) which are known to be symbiotic with ectomycorrhizal fungi. The purpose of this study was to determine the diversity of ectomycorrhizal morphotypes under pine stands in Kendari Botanical Garden. This research was conducted from September to October 2020. The research method used was purposive sampling, including plot making, root sampling and characterisation and identification of root morphotypes. Morphotype characterisation used the colour atlas of ectomychorrizae guide while the percentage of colonisation was calculated using the gridline intersection method. Pinus merkusii formed 7 ectomycorrhizal morphotypes namely simple very pole brown, dichotomous light yellowish brown, dichotomous brownish yellow, monopodial-pinnate reddish black, irregularly pinnate very dark grey, coralloid dark brown and coralloid very dark grey. The simple very pole brown morphotype was the type with the highest relative abundance and species richness index with a root colonisation percentage of 36.43%. The ectomycorrhizal diversity index in P. merkusii is in the high category with a value of 3.45